2009
DOI: 10.1016/j.ab.2008.11.036
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescence resonance energy transfer-based approach for investigating late endosome–lysosome retrograde fusion events

Abstract: Traditionally, lysosomes have been considered to be a terminal endocytic compartment. Recent studies suggest that lysosomes are quite dynamic, being able to fuse with other late endocytic compartments as well as with the plasma membrane. Here we describe a quantitative fluorescence energy transfer (FRET)-based method for assessing rates of retrograde fusion between terminal lysosomes and late endosomes in living cells. Late endosomes were specifically labeled with 800-nm latex beads that were conjugated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Data from previously analyzed fluorescence resonance energy transfer (FRET)-based, late endosome–lysosome fusion assays for quantitation of hybrid organelle formation rates were utilized for this purpose [23]. Data from these experiments were used to obtain rate constants for late endosome to hybrid organelle trafficking as well as lysosome to hybrid organelle trafficking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from previously analyzed fluorescence resonance energy transfer (FRET)-based, late endosome–lysosome fusion assays for quantitation of hybrid organelle formation rates were utilized for this purpose [23]. Data from these experiments were used to obtain rate constants for late endosome to hybrid organelle trafficking as well as lysosome to hybrid organelle trafficking.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that amine-induced vacuoles are merely greatly expanded hybrid organelles, which is consistent with our immunofluorescence evaluations. We have recently developed a FRET-based assay that allows us to quantitatively measure the retrograde fusion of lysosomes with late endosomes [23]. Using this assay, we have shown that the lysosomal membrane protein NPC1 is required for efficient hybrid organelle formation (mutations in NPC1 lead to 95% of cases of Niemann–Pick type-C disease , a fatal neurodegenerative lysosomal-storage disorder) [22,23].…”
Section: Amine-induced Vacuolizationmentioning
confidence: 99%
“…In addition to the failure to export cholesterol from the LEL a variety of experiments have detected multiple transport defects in Niemann-Pick cells (Neufeld et al 1999;Liscum 2000;Choudhury et al 2002;Choudhury et al 2004;Pipalia et al 2007;Kaufmann et al 2009;Tharkeshwar et al 2017) including a slowing of the entire endocytic process (Choudhury et al 2004;Tharkeshwar et al 2017). How can an accumulation of a single metabolite have such wide-ranging effects?…”
Section: Endocytosismentioning
confidence: 99%
“…Because this crosstalk was constant during imaging, it was measured and subtracted from the acceptor emission signal. Following previous protocol (Kaufmann, Goldman, & Krise, 2009), the FRET ratio was calculated as the ratio of the emission intensity of acceptor after crosstalk subtraction $55+&167 to the emission of intensity of the donor 86#67 at the donor excitation (561 nm). In the FRET-ratio-vs-time plot, the slope of the increment portion of the FRET ratio curve, named FRET rate, was used for the quantification of phagosomelysosome fusion rate (Figure 2-figure supplement 2).…”
Section: Single-phagosome Fret-fusion Assaymentioning
confidence: 99%